Advancing working memory research through cortico-cortical transcranial magnetic stimulation - Phylactou, Phivos; Konstantinou, Nikos; Ester, Edward F. (Frontiers in Human Neuroscience, 2024)
The neural underpinnings of working memory (WM) have been of continuous scientific interest for decades. As the understanding of WM progresses and new theories, such as the distributed view of WM, develop, the need to advance the methods used to study WM also arises. This perspective discusses how building from the state-of-the-art in the field of transcranial magnetic stimulation (TMS), and utilising cortico-cortical TMS, may pave the way for testing some of the predictions proposed by the distributed WM view. Further, after briefly discussing current barriers that need to be overcome for implementing cortico-cortical TMS for WM research, examples of how cortico-cortical TMS may be employed in the context of WM research are provided, guided by the ongoing debate on the sensory recruitment framework.